Elevated plasma fibronectin levels associated with venous thromboembolism - Pecheniuk, Natalie M.; Elias, Darlene J.; Deguchi, Hiroshi; Averell, Patricia M.; Griffin, John H. (Thrombosis and Haemostasis, 2008)
Elevated plasma fibronectin levels occur in various clinical states including arterial disease. Increasing evidence suggests that atherothrombosis and venous thromboembolism (VTE) share common risk factors. To assess the hypothesis that high plasma fibronectin levels are associated with VTE, we compared plasma fibronectin levels in the Scripps Venous Thrombosis Registry for 113VTE cases vs. age and sex matched controls. VTE cases had significantly higher mean fibronectin concentration compared to controls (127% vs. 103%, p<0.0001); the difference was greater for idiopathic VTE cases compared to secondary VTE cases (133% vs. 120%, respectively). Using a cut-off of >90% of the control values, the odds ratio (OR) for association of VTE for fibronectin plasma levels above the 90th percentile were 9.37 (95% CI 2.73–32.2; p<0.001) and this OR remained significant after adjustment for sex, age, body mass index (BMI), factor V Leiden and prothrombin nt20210A (OR 7.60,95% CI 2.14–27.0; p=0.002). In particular, the OR was statistically significant for idiopathic VTE before and after these statistical adjustments. For the total male cohort, the OR was significant before and after statistical adjustments and was not significant for the total female cohort. In summary, our results suggest that elevated plasma fibronectin levels are associated with VTE especially in males, and extend the potential association between biomarkers and risk factors for arterial atherothrombosis and VTE.
Keywords: Fibronectin; venous thromboembolism; thrombosis